Dwelling - Michaels, Melissa, 1967- (Harvest House Publishers, 2019)
Our dwellings<U+2014>both our home and body<U+2014>are intricately connected. Each has the potential to inspire the other to be its very best! Your home is where your life happens. Learn how to create a sanctuary that inspires your well-being, so you can experience a greater sense of peace, comfort, and belonging. Your body, including your mind and soul, needs daily nourishment to help you feel healthy and happy. You<U+2019>ll discover simple ways to make self-care a priority in your home. Melissa Michaels wants to show you how meaningful it can be to live a life that nurtures both your home and body. By making a series of small, intentional choices<U+2014>from what you bring into your home to how you shape your daily habits and mind-sets<U+2014>you can create a more rejuvenating environment that equips you to go into the world and accomplish all you set out to do.